Additives for plastics handbook - Murphy, John, 1934 May 23- (Elsevier Advanced Technology, 2001)
Both technically and economically, additives form a large and increasingly significant part of the polymer industry, both plastics and elastomers. Since the first edition of this book was published, there have been wide-ranging developments, covering chemistry and formulation of new and more efficient additive systems and the safer use of additives, both by processors in the factory and, in the wider field, as they affect the general public. This new edition follows the successful formula of its predecessor, it provides a comprehensive view of all types of additives, concentrating m.
Includes index.
Keywords: Plastics -- Additives.; elektronické knihy; electronic books